FORMULASI BUBBLE PEARLS DENGAN PENAMBAHAN PUREE JAMBU BIJI (PSIDIUM GUAJAVA L.) - Sugiarto, Della (Journal of Agritechnology and Food Processing, 2021)
Bubble pearls are a beverage product that is easy to consume and rich in antioxidants and is one of the innovations that can be used to process guava so that it does not rot easily. Bubble pearls are generally made from tapioca flour, sugar and water. This study aims to determine the most preferred bubble pearls formulation based on the sensory attributes of the additives in various forms of guava ingredients. Bubble pearls are made with four types of guava ingredients in the form of puree, flour, extract and paste. Making bubble pearls is added with tapioca flour, sugar and water. The ingredients for guava and tapioca flour use a ratio of 4: 1, 3: 2, 2: 3. The first stage sensory test is based on hedonic ranking of the elasticity, mouthfeel and overall attributes, the results of which are analyzed using two way anova. The second stage of sensory test is a hedonic rating of the attributes of taste, aroma, color, texture and overall, the results of which are analyzed using one way ANOVA. The second stage uses 30 panelists each who are not trained who are identified to like bubble pearls. The results of the first stage sensory test showed that the attributes of chewiness, mouthfeel and overall were guava flour, puree, pasta with a ratio of 4: 1 while the extract form was a 3: 2 ratio. The results of the second stage sensory test showed that the attributes of aroma, taste, texture, color, and overall were guava flour with a ratio of 4: 1. Overall,  the most preferred formulation for making  bubble pears is made from guava powder and tapioca flour with a ratio of 4:1.